Prevalence of Stunting According to WHO Growth Standards and Indonesian Growth Reference Charts: A Descriptive Study from Blega Sub-District - Nafiys Hilmy; Maitsa' Fatharani (Faculty of Medicine, University of Jember, 2021)
Stunting is one of the remaining health issues in Indonesia and its prevalence was still high in the last decades. There are two types of growth charts that can be used in recording the child's growth: growth standards and growth references. In recent times, the selection of the suitable growth charts has become a subject of discussion in many countries. The objective of this study is to describe the prevalence of stunting according to World Health Organization Child Growth Standards (WHOCGS) and Indonesian National Growth Reference Charts (INGRC) of children under five from the Blega sub-district. The secondary data from 2884 children were collected recapitulation of the 'Bulan Timbang' program in February 2020. Z-score of length/height-for-age was plotted according to WHOCGS and INGRC. The result showed that the prevalence of stunting were lower for the INGRC than WHOCGS (5.83% and 11.17%, with p-value <0.001). There was an advantage and disadvantage when using both two growth charts. Further research is still needed to support the result of this study. Keywords: Stunting, World Health Organization Child Growth Standards, Indonesian National Growth Reference Charts